Das Allgemeine im Besonderen – Mechanismen der Obligatorischen Kontrolle am Beispiel des Deutschen - Aptacy, Jarosław (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft, 2019)
The aim of this article is to show which generative mechanisms are responsible for establishing a control relationship between syntactic structures. As a theoretical basis, the Movement Theory of Control by Hornstein was chosen because it has already been tested in numerous languages and has universal character. Its applicability was exemplified by some data of subject and object control in German. For this purpose, some derivations have been outlined. In addition, difficulties that this theory encounters were pointed out. For example, in the derivation of subject control over object, as it exists in the case of promise-verbs.